Enhancing educational support through sports-inspired engagement: exploring factors impacting teacher commitment in special needs schools - Dashi, Marinela; Strigas, Athanasios (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
Teacher engagement in special needs schools is pivotal to the delivery of inclusive, equitable, and high-quality education. This study investigated the multidimensional factors influencing teacher engagement by examining the roles of experience, training, collaboration, Sports involvement, and school resources in special education settings. Utilizing a sample of 850 teachers involved in educational support during the Athens Marathon from 2018 to 2022, the study employed the Structural Equation Modeling (SEM) to test five hypotheses. Results indicated that teacher experience (β = 0.27, p < 0.001), training (β = 0.31, p < 0.001), and collaboration (β = 0.25, p < 0.001) significantly influence student outcomes and teacher satisfaction, while sports involvement and resource availability emerge as critical factors in enhancing emotional development and job contentment. Despite initial model limitations, a refined SEM model offers improved explanatory power, reinforcing the need for adaptive frameworks in assessing teacher motivation and satisfaction. These findings underscore the importance of systemic support, professional development, and stakeholder collaboration in sustaining effective educational practices in special needs environments.